Imaging of COVID-19-associated craniofacial mucormycosis: a black and white review of the “black fungus” - Sanghvi, D. (Clin Radiol, 2021)
A subset of diabetic COVID-19 patients treated with steroids, oxygen, and/or prolonged intensive care admission develop rhino-orbito-cerebral mucormycosis. Radiologists must have a high index of suspicion for early diagnosis, which prompts immediate institution of antifungal therapy that limits morbidity and mortality. Assessment of disease extent by imaging is crucial for planning surgical debridement. Complete debridement of necrotic tissue improves survival. Imaging features reflect the angioinvasive behaviour of fungal hyphae from the Mucoraceae family, which cause necrotising vasculitis and thrombosis resulting in extensive tissue infarction. Contrast-enhanced magnetic resonance imaging (MRI) is the imaging technique of choice. The classic “black turbinate” on contrast-enhanced imaging represents localised invasive fungal rhinosinusitis (IFRS). A striking radiological feature of disseminated craniofacial disease is non-enhancing devitalised and necrotic soft tissue at the orbits and central skull base. Sinonasal and extrasinonasal non-enhancing lesions in IFRS are secondary to coagulative necrosis induced by fungal elements. Multicompartmental and extrasinonasal tissue infarction is possible without overt bone involvement and caused by the propensity of fungal elements to disseminate from the nasal cavity via perineural and perivascular routes. Fungal vasculitis can result in internal carotid artery occlusion and cerebral infarction. Remnant non-enhancing lesions after surgical debridement portend a poor prognosis. Assessment for the non-enhancing MRI lesion is crucial, as it is a sole independent prognostic factor for IFRS-specific mortality. In this review, we describe common and uncommon imaging presentations of biopsy-proven rhino-orbito-cerebral mucormycosis in a cohort of nearly 40 COVID-19 patients.